2021
DOI: 10.1089/end.2016.0237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Single-Use Flexible Ureteroscope

Abstract: The LithoVue Single-Use Digital ureteroscope has comparable optical capabilities, deflection, and flow, making it a viable alternative to standard reusable fourth-generation flexible digital and fiberoptic ureteroscopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
3
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 15 publications
2
50
3
2
Order By: Relevance
“…Therefore flexible ureteroscopes (FURS) are introduced to the urinary tract and guided to the stone's site where laser application and hence calculi destruction takes place 4 . Different kinds of flexible multi-use endoscopes are available on the market: conventional FURS, in which the image is delivered via a fibre bundle, FURS with attached camera system for image acquisition, and novel digital FURS with "chip on the tip" technology 5,6 . During the last few years huge improvements proceeded to image quality, durability, irrigation flow and reduction of the shaft diameter 3,4,7 , and thus evolved the ureteroscopic Ho:YAG laser lithotripsy to a safer and highly efficient method for calculi destruction 2,8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore flexible ureteroscopes (FURS) are introduced to the urinary tract and guided to the stone's site where laser application and hence calculi destruction takes place 4 . Different kinds of flexible multi-use endoscopes are available on the market: conventional FURS, in which the image is delivered via a fibre bundle, FURS with attached camera system for image acquisition, and novel digital FURS with "chip on the tip" technology 5,6 . During the last few years huge improvements proceeded to image quality, durability, irrigation flow and reduction of the shaft diameter 3,4,7 , and thus evolved the ureteroscopic Ho:YAG laser lithotripsy to a safer and highly efficient method for calculi destruction 2,8 .…”
mentioning
confidence: 99%
“…In the present study a disposable flexible endoscope (PU3022A, Zhuhai PUSEN Medical Technology, Zhuhai, Guangdong China) 16 was systematically tested with special interest in the image quality in terms of spatial resolution and distortion, as well as the maximal bending capability and the irrigation flow. Data were compared to published results 5,17 and two reusable flexible endoscopes currently used in the operating room, a video FURS with attached camera system (FLEX X C , KARL STORZ SE & Co. KG, Tuttlingen Germany) and a fiberoptic FURS device (FLEX X 2S , KARL STORZ SE & Co. KG, Tuttlingen Germany). Additionally destruction tests were performed with one single-use device, whereby the application fibre was withdrawn from +10 mm distance in respect to the working channel outlet to (−2 mm) inside the endoscope.…”
mentioning
confidence: 99%
“…Still, inherent limitations need to be acknowledged. Dale et al [7] have recently published an in vitro study comparing 2 state of the art reusable scopes with a disposable one and have noted a loss of deflection ranging from 2 to 27 degrees on the reusable scope depending on the auxiliary instrument inserted. Conversely, Boylu et al [8] all in an earlier study have demon-Urol Int 2020;104:437-444 DOI: 10.1159/000502759 strated that the disposable scope they compared against reusable ones demonstrated the highest loss in flexion characteristics (35.7% down and 39.3% up), with a similar deficiency in flow rates.…”
Section: Discussionmentioning
confidence: 99%
“…There are many single‐use digital fURS already on the market, including LithoVue (Boston Scientific, Marlborough, MA, USA), PU3022A (Pusen, Zhuhai, China), Polyscope (Lumenis, Yokneam, Israel, Polydiagnost, Hallbergmoos, Germany), Semi‐Flex Scope (Maxiflex, Los Angeles, CA, USA), FlexoVue (Cook Medical, Bloomington, IN, USA) and Yc‐FR‐A (YouCare Tech, Wuhan, China) . In vitro testing has shown that single‐use scopes have equivalent optics, deflection ability and working channel flow rates to more expensive reusable scopes …”
Section: Introductionmentioning
confidence: 99%
“…11 In vitro testing has shown that single-use scopes have equivalent optics, deflection ability and working channel flow rates to more expensive reusable scopes. [12][13][14][15][16][17] In vivo testing has been limited. A European multicenter evaluation of the single-use LithoVue in 40 procedures found that operators rated the image quality as "good" or "very good" in 95% of cases.…”
Section: Introductionmentioning
confidence: 99%